Narrative and Reading Comprehension Performance in Dyslexic Persian Students - Farshad khazraie; Salimeh Jafari; Maryam Jalalipour (Shiraz University of Medical Sciences, 2023)
BACKGROUND: Through research on the role of storytelling skills in building learning and writing elements, little attention has been paid to assessing strengths and weaknesses in story structure, especially microstructure, in dyslexic students. The purpose of this study is to assess the role of this structure as a manifestation of the verbal and cognitive performance of these students.Method: This is a descriptive analysis study. To identify dyslexic students, the Screening test for dyslexia diagnosis by Shafii et al. and Shirazi-Nilipour's reading diagnostic test were used. A total of 31 dyslexic students at secondary elementary school were identified during testing, and the remaining subjects (n = 35 students) were assigned to the control group. The story retelling test was used to assess students' storytelling skills. A parametric test (independent-samples t-test) was used to compare normally distributed data. A nonparametric test (Mann-Whitney U test) was used for non-normal data. Pearson's correlation test was also used to examine correlations for normally distributed data, and Spearman's correlation test was used for non-normal data.Results: Students with dyslexia had significantly lower mean scores in all substructures of the macrostructure, including topic maintenance, sequence of events, and the main information. They also had significantly lower microstructure scores, including mean length of utterance, conjunction use, and syntactic complexity, compared to their normal counterparts  (p<0.05).Conclusion: Dyslexic students perform worse than their peers on most micro- and macrostructures of the retelling test. In other words, these students have poor linguistic and cognitive prerequisites for understanding and mastering reading skills. On the other hand, the results show that there is a meaningful association between storytelling skills and subsequent reading and comprehension acquisition.